(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This article analyzes the merits of the first national publication of the Fergana Valley “Sadoi Turkestan” in the development of the nation, as well as articles written by the publisher and editor of the newspaper Obidjon Makhmudov.